The Value Chain Governance of Robusta Coffee in Bogor Regency - Harmini; Suryana, Anggita; Harianto; Syaukat, Yusman (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The governance structure is critical in coffee value chain development. An effective coffee value chain governance is expected to improve efficiency, reduce costs, and increase innovation while benefiting consumers and society. This research aims to analyze the governance structure of the robusta coffee value chain in Sukamakmur District, Bogor Regency, West Java. The study employed survey data from 41 actors along the robusta coffee value chains. Kind of actors are farmers, intermediaries, and downstream actors. The data was analyzed using Gereffi’s value chain mapping and governance analyses. The study revealed that the robusta coffee value chain actors consist of farmers, small-scale traders, large-scale traders, regional traders, coffee processing companies, retailers, roasteries, and cafés. Every actor along the coffee value chain has different activities that add value and differentiate the coffee products. The findings indicated that the Robusta coffee value chain governance is categorized as market governance with low information complexity, high information codifiability, and high supplier capability. To strengthen the governance, it is necessary to establish a partnership with downstream actors and carry out intervention from lead firms, to improve coordination among value chain actors and increase coffee quality. Keywords: chain actor, coffee value chain, lead firm, market governance, robusta coffee